PENGARUH PENGETAHUAN INVESTASI, KEMAJUAN TEKNOLOGI, DAN DAYA DUKUNG KAMPUS TERHADAP MINAT INVESTASI - Musa, Fernanda Bagas; Sundari, Siti (Yayasan Education and Social Center, 2024)
This study examined the effect of investment knowledge, technological progress, and campus support capacity on student investment interest. The subjects in this study were accounting students at the National Development University